(untitled) (Research, Society and Development, 2021)
Objective: The new coronavirus (COVID-19) belongs to a family of viruses that has a high mutation capacity in animals. SARS-CoV-2 follows the pattern of the most vulnerable individuals, such as the elderly and adults with chronic diseases, with the lowest number of victims, children. The present study aimed to identify the possible nursing diagnoses and present a care plan, through the application of the nursing process, to patients with mild and severe manifestations of COVID-19, using the NANDA/NOC/NIC taxonomy. Methodology: This is a literature review, exploratory and bibliographic research. Information regarding the signs and symptoms of the disease was obtained by publications indexed in the Databases Latin American and Caribbean Literature on Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO), following the inclusion and exclusion criteria. Results: It is noted that the most frequent manifestations in mild and severe cases are runny nose, dyspnea, fatigue, fever, myalgia, nasal obstruction and cough. According to the clinical findings, a possible care plan was developed for these patients. Conclusion: It is concluded that nursing professionals compose the front line in combating and controlling the spread of infection by the new coronavirus. Thus, they play a fundamental role in patient health care and, therefore, need to perform planned and evidence-based care.